2010
DOI: 10.1111/j.1365-2222.2010.03554.x
|View full text |Cite
|
Sign up to set email alerts
|

How do we know when peanut and tree nut allergy have resolved, and how do we keep it resolved?

Abstract: Over the last two decades, the prevalence of peanut and tree nut allergy has increased throughout the western world. Adverse reactions to these foods account for over 50% of all deaths resulting from food-related anaphylaxis. Until recently, evidence suggested that all peanut and tree nut allergy were permanent. It is now known that about 20% and 10%, respectively, of young patients outgrow peanut and tree nut allergies. Achieving tolerance is associated with increasing circulating T regulatory cells and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Peanut allergy tends to be persistent [8] with a 10-year remission rate of less than 20% [9]. Avoidance of peanuts cannot be guaranteed and accidental ingestion may be dangerous or even fatal [10].…”
Section: Introductionmentioning
confidence: 99%
“…Peanut allergy tends to be persistent [8] with a 10-year remission rate of less than 20% [9]. Avoidance of peanuts cannot be guaranteed and accidental ingestion may be dangerous or even fatal [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown a correlation between the concentration of allergen-specific IgE and the probability of clinical reactivity [15, 16]. Lower IgE levels are associated with earlier resolution of food allergy, and the rate of the decrease of serum IgE levels can be a predictor of when challenges are appropriate [21, 22]. However, without a history of a suspected allergic reaction, a "diagnostic" point alone cannot be used to diagnose a definite food allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Using SPT to test for allergies is not considered quantitative and is used only to determine the presence or absence of an allergy. However, this test is not always an infallible method for determining allergy, for patients with atopic dermatitis may develop false-positive wheals [12]. Subjects must also abstain from using drugs, such as antihistamines, that will affect the results of the test.…”
Section: Skin Prick Testmentioning
confidence: 96%
“…In this type of study, the subjects are required to consume foods that may potentially cause an allergic reaction. This can prove dangerous, since patients must be directly subjected to allergens, and those who are susceptible to anaphylaxis should not be included in this type of study [12]. Perry et al [88] tested the safety of OFC studies and found that 28% of OFC participants had severe reactions.…”
Section: Oral Food Challengementioning
confidence: 98%